Risk Management Model of the Islamic Ethical Practice Dimension (i-EP) - Hasyim, Diana; Budiarta, Kustoro; Lubis, Nurul Wardani; Parulian, Edison; Syarif, Shamir Hashim (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Adoption of Sharia Compliance (SC) is one of the dimensions of Islamic Ethical Practice (i-EP) or Islamic Corporate Social Responsibility (i-CSR), which can potentially lead companies to obtain several significant capital market benefits, including affecting risk (cost of equity). However, whether and to what extent SC influences the cost of equity is still an issue and has yet to be widely documented at the theoretical and empirical levels, especially in the Indonesian context. Apart from the low level of cash holding, the evidence gap shows that the Indonesian Sharia financial screening criteria are more liberal than the international criteria, which indicates that Indonesian SC leverage contains a higher financial risk premium, thus possibly having implications for estimating the high expected return of investments and in turn the effect of SC on the cost of equity potentially has different empirical significance from international finding. Implications of liquidity and risk premium on the cost of equity indicate that SC's influence on the cost of equity is more complex than simple causality. Therefore, it is necessary to build a more comprehensive system by formulating contingency factors in the relationship between SC and the cost of equity. The finding reveal from 891 observations that the link between SC and cost of equity is fully mediated relationship, which indicates that SC can only affect the cost of equity with good reputation and by improving performance.